Insectos dulceacuícolas depositados en la Colección Limnológica de la Universidad de Antioquia, CLUA-035 (2016)
The database of aquatic insects collected from freshwater systems in the departments of Antioquia, Arauca, Bolívar, Boyacá, Caldas, Cauca, Córdoba, La Guajira, Santander and Sucre is described. The biological material presented here was part of different projects, such as environmental consulting, as well as field sampling by both undergraduate and postgraduate students from the Institute of Biology, University of Antioquia. The Antioquia’s University Limnology Collection, CLUA-035 has 3209 standardized lots published in online databases that are distributed among 11 orders, 91 families and 235 genera. However, Neuroptera and Orthoptera orders were not identified to lower taxonomic levels.